Genetic differentiation of red and gray tilapia (Oreochromis niloticus) using microsatellites and SCAR markers as indicators of genetic sex - Arqueros, Monica (2017)
The aims of this work was to develop a standardized molecular protocols, to differentiate red and gray tilapia lineages using DNA microsatellites and to evaluate SCAR-5F-X/5R and SCAR-5F/5R-Y markers associated with the phenotypic sex of O. niloticus. The UNH106 microsatellite allowed differentiating genetically the lineages of red tilapia from gray. The markers UNH136, UNH115 and UNH995 presented monomorphic loci in both the red and gray tilapia in the population stock of the Centro Experimental de Genética of the Universidad Nacional de Trujillo. Fragment sizes for microsatellites and the reference gene β actin are described. The effectiveness of SCAR markers as informative in the determination of the genetic sex in XX and YY females and XY y YY males of red tilapia and XX females and XY males of gray tilapia was also confirmed.